ORGANIC POLLUTANTS IN THE GROUNDWATERS USED FOR IRRIGATION PURPOSE WITHIN A COAL-BEARING BASIN OF NORTHERN GREECE - Iordanidis, A.; Schwarzbauer, J.; Gudulas, K. (Bulletin of the Geological Society of Greece, 2016)
The aim of this study is to identify potential toxic or environmentally relevant organic compounds in the aquifers of the Amynteo hydrogeological basin and to investigate a possible link of the identified organic contaminants with the Pliocene Amynteo lignites. For these purposes ten groundwater samples were collected from this area. A sequential liquid-liquid extraction procedure was applied to approximately 1000 mL aliquots of the groundwater samples using dichloromethane as extractant. All extracts were analysed by Gas Chromatography (GC) and Gas-Chromatography-Mass Spectrometry (GC-MS) by means of a non-target screening approach. The results of the GC-MS analyses of the extracts are presented and discussed in this work. The identified organic compounds with a potential environmental relevance are: 2, 2, 4 trimethyl-1, 3- pentanediol diisobutyrate (TXIB), triacetine, isopropyl palminate, isopropyl myristate, tributyl-, triethyl- and trioctylphosphates, N, N-dibutyl formamide, methyl dihydrojasmonate, nonylphenols and bumetrizole. However, all these organic micropollutants can derive either by anthropogenic emissions (plasticizers, industrial pollutants, pesticides etc.) or by contaminations from the pump and the borehole structure itself. Noteworthy, coal derived organic molecules (such as anthracene, fluorene, pyrene, phenanthrene etc.) have not been detected. Hence, an influence of coal deposits to the groundwater quality is considered negligible.